Control of PC Remotely Via Android Application - B. , Sreelekha; R. , Lalitha; V. , Mukesh; E. , Ramki; N. , Vasanth (International Journal of Psychosocial Rehabilitation, 2020)
The evolution of mobile devices, especially in these modern days, has drastically changed the face of business. A mobile phone device is often expected to offer computer-like functionality. These days, most mobile phone users find it somehow inconvenient to do some tasks using their computers. Most individuals prefer to change positions while sitting and stretching and also feel a bit more comfortable when browsing through their computers. It can be very impractical to be confined to the keyboard and mouse while sitting 5 or 10 feet from the computer. Hence, the proposed application is meant to turn the hand cellphone into a wireless keyboard and mouse with a touch-pad. Also, the system provides the features to access the files available in the computer; if the file seems to be a media file, this Android app can play, pause, stop, mute, and enable/disable full-screen mode of the respective media. The connection establishment is made through the wireless network (WiFi). This prototype is proven to be able to perform most of the actions a normal computer can perform.